Adaptation and Validation of the Satisfaction With Life Scale (SWLS) - Ekayanti, Ni Luh Hita; Haq, Muhammad Imanul; Pratma, Rendi Kurnia; Suryani, Nadya Ali; Prasetya, Yudha Tri; Sahrah, Alimatus; Anwar, Anwar (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Life satisfaction is an individual's cognitive evaluation of their overall quality of life, which is becoming increasingly important to understand in the context of Generation Z working amidst the dynamics of rapid social and technological change. This study aims to adapt and test the psychometric quality of the Indonesian version of the Satisfaction With Life Scale (SWLS) in the working Generation Z population. The study population was Generation Z (born 1997–2012) who worked full- or part-time, with a sample of 301 subjects obtained through accidental sampling techniques. The adaptation process was carried out following the ITC Guidelines for Translating and Adapting Tests, including forward translation, back translation, expert review with an Aiken's V value of 0.70–0.85 for each item, and a readability test. Data analysis involved reliability testing and Confirmatory Factor Analysis (CFA). The results of the reliability test showed good internal consistency with a Cronbach's Alpha value of 0.805. The CFA results confirmed an excellent fit of the single factor OR unidimensional model, with all items loading significantly (Standardized Factor Loading 0.577–0.772), as well as strong model fit indices (CFI = 1.00; TLI = 1.01; RMSEA = 0.00)